Antecedentes e consequentes da satisfação com a prática do Crossfit na perspectiva da lógica dominada por serviço - Clárison Gonçalves Gamarano (2020)
Throughout history, the manner of perceiving and applying Marketing has undergone profound transformations. Once it is a rather fragmented phenomenon and is still in the process of formation, Vargo and Lusch (2004) proposed an integrative and comprehensive logic for the understanding of exchanges and their related events: the service-dominated logic (S-DL). This logic represents a contrast to the traditional logic, which would not be able to explain all aspects involved in transactions in the current social and economic contexts. In order to contribute to empirical applications, this project tested a quantitative model, whose focal construct is the consumer satisfaction, throughout the prism of this new logic. For this, Crossfit, which represents a growing phenomenon, however it is also a little explored subject, was used as a basis for the validation of the S-DL precepts, especially with regard to those aspects involved to the co-creation thematic, an essential factor for the proper formulation of marketing strategies. Structural equation modeling was used to calculate the impacts between the model's constructs. As a result, six of those seven hypotheses contained in the proposed model were supported. In a nutshell, the positive impact of service quality on co-creation and perceived value was proven, as well as the positive impact of co-creation on perceived value and satisfaction. In addition, satisfaction positively impacted the word of mouth communication. These results provided advances to the state of the art in all aspects that make up the studied phenomenon, are they: consumer satisfaction, co-creation of value, S-DL and Crossfit. In the managerial scope, stands out the possibility of obtaining competitive advantages for companies that observe consumer behavior through the resolutions reached in this study.